Relationship between macroeconomic fundamentals and finance sector of stock market: evidence from Bursa Malaysia / Muhammad Baihaqi Kamal - Kamal, Muhammad Baihaqi (2016)
Purposely this study is to determine the relationship between the selected macroeconomic variables includes economic activity, inflation rate, interest rate, exchange rate and money supply and finance sector of Bursa Malaysia. The data is time series data covering the period from 2007 to 2015 by using monthly data. The research intends to focus on methodology of data analysis namely Ordinary Least Square (OLS). The application of Ordinary Least Square (OLS) method is to examine the relationship between the selected macroeconomic variables includes economic activity, inflation rate, interest rate, exchange rate and money supply on finance sector of Bursa Malaysia. The dependent variable is finance sector of Bursa Malaysia and independent variables are economic activity, money supply, inflation rate, interest rate and exchange rate.